Taking Precaution in Case of Obligatory Usury: A Contemporary Applied Jurisprudential Study (Mutah Journal of Humanities and Social Sciences (MJHSS), 2025)
This study dealt with one of the jurisprudential rules related to precaution: the rule of taking precaution when usury is obligatory. The researcher explained the meaning of the rule in particular and in general, and explained the evidence related to it from legal texts that establish the foundations of the rule, as pioneered by Al-Izz bin Abdul Salam 25/ 862, and that proves its legitimacy. The study also focused on highlighting the role of the rule in absorbing new applications and calamities related to contemporary investment formulas, proving that the Islamic law is realistic so that it keeps pace with people’s lives and accommodates all emerging issues, in a way that meets people’s interests and removes hardships that may face them.
Keywords: Rule; Jurisprudence; Precaution, Usury